Robotic-assisted tracheobronchial surgery - Cohen, Brian D. (J Thorac Dis, 2020)
Robotic technology is positioned to transform the approach to tracheobronchial surgery. With its magnified 3D view, intuitive controls, wristed-instruments, high-fidelity simulation platforms, and the steady implementation of new technical improvement, the robot is well-suited to manage the careful dissection and delicate handling of the airway in tracheobronchial surgery. This innovative technology has the potential to promote the widespread adoption of minimally invasive techniques for this complex thoracic surgery.